2022
DOI: 10.3390/toxins14010033
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Seasonal Monitoring of Domoic Acid in Three Shellfish Species from the Northern Adriatic Sea

Abstract: As filter feeders, bivalves and ascidians can accumulate contaminants present in the environment and pass them on to higher food chain levels as vectors. The consumption of bivalves contaminated with the potent neurotoxin domoic acid (DA) can cause amnesic shellfish poisoning in humans. The aim of this study was to determine seasonal differences in occurrence and accumulation of this phycotoxin in European oysters (Ostrea edulis Linnaeus, 1758) (n = 46), Queen scallops (Aequipecten opercularis Linnaeus, 1758) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Despite the substantial differences in DA accumulation, the concentrations in the five groups of shellfish samples did not exceed the 20,000 µg/kg regulatory level standard. DA was also present in 36.00% of European oysters, Queen scallops and ascidian samples in the northern Adriatic Sea, where DA concentrations ranged from 0-810 µg/kg [25]. In Lebanese coastal waters, at the same latitude as China, DA concentrations ranged from 150-3880 µg/kg in different shellfish samples [53].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the substantial differences in DA accumulation, the concentrations in the five groups of shellfish samples did not exceed the 20,000 µg/kg regulatory level standard. DA was also present in 36.00% of European oysters, Queen scallops and ascidian samples in the northern Adriatic Sea, where DA concentrations ranged from 0-810 µg/kg [25]. In Lebanese coastal waters, at the same latitude as China, DA concentrations ranged from 150-3880 µg/kg in different shellfish samples [53].…”
Section: Discussionmentioning
confidence: 98%
“…Studies have shown that different shellfish accumulate different levels of DA in their tissues [20,24], probably due to different accumulation and elimination rates and differences in the distribution of DA in the various tissues [25]. In many bivalves, most of the DA accumulates in the digestive gland, which is the main site of metabolic elimination [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, profound inter-specific variability in the toxicokinetics of accumulation and depuration rates of DA burdens have been reported between several invertebrate species in the same affected area (Costa et al, 2004(Costa et al, , 2005aBogan et al, 2007a,b,c;Lage et al, 2012;Ben haddouch et al, 2016;Dusek Jennings et al, 2020;Blanco et al, 2021;Kvrgić et al, 2022). Thus, invertebrates have been broadly classified as "fast" or "slow" DA-depurators (Blanco et al, 2002a,b;Basti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%